State of the Science in Ovarian Cancer Quality of Life Research: A Systematic Review. Issue 7 (1st September 2012) - Hess, Lisa M.; Stehman, Frederick B.
Abstract : Introduction: Health-related quality of life (HRQOL) has become an increasingly important focus of outcomes in cancer care with the movement toward more patient-oriented research. Quality-of-life outcomes are important in ovarian cancer, which has not yet benefitted from improved survival outcomes as have other diseases. This study was designed to systematically assess and summarize HRQOL in ovarian cancer. Methods: A systematic search strategy was initiated to identify published literature measuring HRQOL of women with a diagnosis of ovarian cancer (OC). Data were synthesized to evaluate HRQOL and patient-reported outcome data at various time points: before, during, and after chemotherapy. Data were pooled and summary statistics compared across published studies. Comparisons of means were conducted using analysis of variance. Results: There were 170 publications meeting all eligibility criteria, representing 139 unique studies of patients with ovarian cancer, where QOL data were collected. Within this literature, more than 90 different patient-reported outcome (PRO) instruments were administered. The most common HRQOL instruments included the European Organisation for Research and Treatment of Cancer QLQ-C30 and the Functional Assessment of Cancer Therapy. Few studies alone demonstrated significant differences in QOL between the experimental and comparison arm or throughout the treatment period. Pooled data, however, show that baseline QOL may significantly improve, particularly after completion of chemotherapy treatment. Discussion: Despite the increase in assessment and reporting of QOL in ovarian cancer research studies during the past 15 years, there remains little consistency in the types and format of data collected. There is a need to enhance the standardized collection and reporting of HRQOL data from research involving women with ovarian cancer so that research can build on the cumulative knowledge base to improve outcomes in this patient population.